Governance and sustainability in Southeast Asia - Tran, Mi; Beddewela, Eshani; Ntim, Collins G (Accounting research journal, 2021)
Purpose This paper aims to examine the relationship between a diverse set of corporate governance (CG) mechanisms and corporate sustainability disclosure (CSD) in Southeast Asian countries under national stakeholder reform. Design/methodology/approach Data analysis is based on 171 of the largest companies across six Southeast Asian countries using a 30-item CSD measure. Findings The authors find that there are wide variations in the levels of CSD across the countries. The findings indicate that board size, board gender diversity, block ownership and the presence of a sustainability committee are significant determinants of CSD. Additionally, whilst more stringent stakeholder governance reform motivates firms to publish more sustainability information, it fails to influence the effectiveness of the board of directors in promoting CSD. Practical implications Findings of this study highlight the essential role internal governance structure plays in monitoring corporate actions and enabling corporations to reduce their legitimacy gap. The findings further encourage regulators and policymakers to question, with utmost importance, the effectiveness of stakeholder reform in making significant organisational changes. Originality/value There is a dearth of studies that examine the CG-CSD nexus in relation to specific institutional characteristics. Existing studies mainly focus on a single country with similar institutional environments and thus limiting the ability to understand the “context specificity” of sustainability content development. This paper provides an overview of stakeholder reform in Southeast Asian countries and empirically substantiates the relationship between CG and CSD across six countries undergoing such reforms in the region.